Eco-Solutioning: The Design and Evaluation of a Curricular Unit to Foster Students’ Creation of Solutions to Address Local Socio-Scientific Issues - Songer, Nancy Butler; Ibarrola Recalde, Guillermo D. (Frontiers in Education, 2021)
The global pandemic and climate change have led to unprecedented environmental, social, and economic challenges with interdisciplinary STEM foundations. Even as STEM learning has never been more important, very few pre-college instructional programs prepare students to address these challenges through an emphasis on socio-scientific issue (SSI) problem solving and the engineering design of solutions to address local phenomena. The paper discusses the design and evaluation of a pre-college, SSI curricular unit where elementary-age student learning is applied to the generation of solutions to increase biodiversity within local urban neighborhoods. The learning approach, which we call eco-solutioning, builds from current vision and policy documents in STEM education emphasizing phenomenon-centric instructional materials, science investigations, and engineering design. The paper outlines design principles for creating an eco-solutioning instructional unit that guides young students to: (a) study local organisms, (b) use an engineering design approach to craft solutions to increase local biodiversity, and (c) present their solutions to local city planners and community members. Two cycles of research studies evaluated student learning using paired t-tests. Results demonstrated significant pre-post learning outcomes in both research cycles. A third research cycle in the form of a summer extension program supported students as they implemented their local solutions. Conclusions highlight design principles for the successful creation of SSI curricular units centered on local environmental issues of interest to students, teachers, and stakeholders.